Avaliação do grau de conhecimento e de aplicação das práticas do Quick Response Manufacturing : estudo comparativo transnacional - Marchesini, Antonio Gilberto (Universidade Federal de São Carlos, 2015)
In recent decades, the lead time reduction has become crucial to ensure the competition of enterprises. To address this, plus the abandonment of the tradit ional mindset based on efficiency and cost, to a mentality based on the reduction of lead time, companies began to incorporate in production management, principles and practices related, outstandingly, to the Quick Response Manufacturing (QRM) and the Lean Manufacturing (LM). In this context, this work aims, according to companies located in Brazil, Europe, and in the USA: (I) Verify if the degree of knowledge of the exclusive principles of QRM approach is equal to the degree of knowledge regarding common concepts to LM and QRM, (II) Verify if the degree of knowledge of the exclusive principles of QRM is greater due to factors such as training, dissemination, and awareness, (III) Check if the mindset based on economies of scale and cost reduction is still the main obstacle in the degree of knowledge of the companies surveyed, (IV) Verify if the concepts / elements / exclusive practices QRM less adopted by companies are those related to the change of economies of scale and cost-based mindset, still fairly entrenched in enterprises, (V) Verify if there is a significant difference between the degree of implementation of QRM practices due to the region studied, and (VI) Check whether the use of concepts / elements / practices of LM favors the adoption of QRM. For this, it was carried out an exploratory survey with an intentional sample of companies in these regions who wish to reduce the lead time. Data were analyzed using descriptive statistics and non-parametric tests. Concerning to the knowledge of the companies surveyed about the QRM, it was concluded that the level of knowledge about the exclusive practices of QRM is lower than in relation to the common practice at LM and QRM. The companies’ knowledge degree about the exclusive principles of QRM is possibly greater due to training, dissemination, and awareness and such factors are present more at the region of US. The mindset based on economies of scale and cost reduction is possibly the main barrier in the degree of knowledge in the companies surveyed. Concerning to the application of the QRM practices by companies surveyed, it was concluded that the extent of implementation of practices regarding the key concept "power of time" is lower than the other key concepts; there was not observed any statistically significant differences in the degree of implementation of QRM practices due to the region; the LM practices helps and contribute to the effort of implementation of QRM in companies that seek to reduce the lead time and; the concepts, elements and practices of QRM less adopted by companies are those related to the abandonment of the mindset based on economies of scale and cost reduction.
Evaluating the extent of knowledge and application of Quick Response Manufacturing practices : a cross-nation study
Keywords: Manufatura responsiva; Produção enxuta; Conhecimento; Quick Response Manufacturing; Lean manufacturing; Survey; ENGENHARIAS::ENGENHARIA DE PRODUCAO